Fabrication of a complete denture using a modified custom tray with a closed-mouth impression on a fully edentulous compromised mandibular flat ridge - Jhonson; Ismet Danial Nasution; Ricca Chairunnisa (Indonesian Journal of Prosthodontic, 2026)
Background: Severe mandibular alveolar ridge atrophy, common in geriatric patients, compromises the functional success of complete dentures due to a reduced denture-bearing area and the proximity of muscle attachments to the ridge crest. This condition increases denture displacement during function in both horizontal and vertical movements, leading to poor retention and stability of the denture. Accurate impression techniques are critical to overcoming these challenges. The closed-mouth functional impression technique allows for the recording of denture-bearing areas and peripheral seal under functional pressure, potentially enhancing retention.Objective: This case report aims to describe the procedure for fabricating a complete denture using a modified custom tray with a closed-mouth impression on a fully edentulous, compromised mandibular flat ridge.Case Report: A 52-year-old woman presented with a loose and poorly fitting lower denture. Clinical examination revealed complete edentulism with a severely resorbed mandibular ridge. A custom tray was fabricated with a detachable handle to support the closed-mouth impression technique without interfering with occlusion during border molding and impression-making. The closed-mouth approach allowed for better muscle molding, recording of functional borders, and a more accurate reflection of the patient’s oral dynamics. As a result, the final denture exhibited significantly improved retention and comfort during function. This case highlights the clinical advantage of the closed-mouth impression technique in managing challenging ridge conditions and emphasizes the practical benefit of modifying tray design to ease the procedure for both clinician and patient. Such adaptation is especially relevant in geriatric care, where functional and anatomical limitations are common.Conclusion: The use of a modified custom tray with the closed-mouth functional impression technique proved effective in managing a severely resorbed mandibular ridge. It resulted in a stable, retentive, and comfortable complete denture, contributing to enhanced patient satisfaction.